Characterization of aged rat vocal fold fibroblasts. (19th November 2018) - Kawai, Yoshitaka; Kishimoto, Yo; Sogami, Tohru; Suzuki, Ryo; Tsuji, Takuya; Hiwatashi, Nao; Tateya, Ichiro; Kanemaru, Shin‐Ichi; Nakamura, Tatsuo; Omori, Koichi; Hirano, Shigeru
Abstract : Objectives/Hypothesis: To elucidate the aging physiology of the vocal folds, we examined the characters of aged vocal fold fibroblasts (VFFs) in various conditions. Study Design: In vitro study. Methods: VFFs from young (12‐week‐old) and aged (19‐month‐old) Sprague‐Dawley rats were compared. Proliferative capacity, ratio of myofibroblast to fibroblast, myofibroblast function, and extracellular matrix production were examined in the following conditions: naïve, basic fibroblast growth factor (bFGF) supplemented, and hepatocyte growth factor (HGF) supplemented. Results: Aged VFFs demonstrated reduced proliferation by cell counting, though the ratio of Ki‐67–positive cells showed no difference. Aged VFFs exhibited an increased expression of α‐smooth muscle actin (α‐SMA); however, they demonstrated no enhanced contractile ability in a gel contraction assay. Type I collagen protein was increased age dependently, accompanied with decreased Mmp1 and unchanged Col1a1 transcription. Type I collagen protein and α‐SMA represented quite similar reduction patterns to bFGF or HGF administration. Conclusions: The following possible characteristics of aged VFFs were implied: long duration of mitosis, increased myofibroblast population size with certain dysfunctions, reduced type I collagen turnover, and correlation between α‐SMA expression and type I collagen metabolism. Further investigations of these features will help to clarify presbyphonia's pathology and establish treatment strategies. Level of Evidence: NA Laryngoscope, 129:E94–E101, 2019